An attempt to Stimulate lipids for Biodiesel Production from locally Isolated Microalgae in Iraq - Baghdad Science Journal (مجلة بغداد للعلوم)
Two locally isolated microalgae (Chlorella vulgaris Bejerinck and Nitzschia palea (Kützing) W. Smith) were used in the current study to test their ability to production biodiesel through stimulated in different nitrogen concentration treatments (0, 2, 4, 8 gl ), and effect of nitrogen concentration on the quantity of primary product (carbohydrate, protein ), also the quantity and quality of lipid. The results revealed that starvation of nitrogen led to high lipid yielding, in C. vulgaris and N. palea the lipid content increased from 6.6% to 40% and 40% to 60% of dry weight (DW) respectively.Also in C. vulgaris, the highest carbohydrate was 23% of DW from zero nitrate medium and the highest protein was 50% of DW in the treatment 8gl. While in N. palea the highest carbohydrate was 25% of DW in the treatment 4gl, and the highest protein was 15% of DW in 8gl treatment.